Relationship Between Nutritional Status, Physical Activity, Type of Work and Smoking Activity with Fitness Level Measured by 6-Minute Walking Test on Non-staff Employees of Universitas Indonesia, Depok - Menaldi Rasmin; Hilma Nur Faiza; Kemal Akbar Suryoadji; Neny Husnaini Zain; Sakinasha Siva Utami; Feni Fitriani Taufik; Dewi Friska; Nani Cahyani Sudarsono; Elisna Syahrudin (Respiratory Science, 2023)
Background: Fitness is inextricable to health and has a significant correlation with the habits and behaviour of individuals such as dietary practice, sedentary behaviour, physical activities, and smoking habits. Many ways can be used to assess an individual fitness level, one of them is using the 6-minute walking test. This study aims to find the correlation between smoking intensity, nutritional status, occupation, and physical activity with the fitness level of outdoor janitors in Universitas Indonesia, Depok. Method: The research method was the cross-sectional design. The determination of the subjects was carried out by a consecutive sampling method. The data obtained results from the assessment of nutritional status, occupation, physical activity, and smoking intensity, as well as result from the 6-minute walking test. Univariate data analysis was used to assess the distribution of subjects based on sociodemographics, nutritional status, physical activity, occupation, and smoking activity. Furthermore, categorical correlative tests used were Man-Whitney, Kruskal-Wallis, and Fisher's Exact test. Results: The subjects obtained are 109 outdoor janitors from UI, Depok in which 59.6% age 18-44 years old, and 56% are male. Based on the correlative test between the fitness level and the nutritional status, value of P=0.086, as value of P between the physical activity and the fitness level is 0.0523. No significant correlation between fitness level and occupation based on location of the job, duration of work and based on the work time (P=1.00; P=1.00; P=0.108) The correlation between smoking intensity with the fitness level has value of P=0.681. Conclusion: There is no significant correlation between nutritional status, physical activity, type of work, and smoking intensity with the fitness level as measured by the 6-minute walking test method for outdoor janitors of UI, Depok.